Conceptions of health promotion in the perspective of mental health professionals - Aguiar, Maria Isis Freire de; Silva Júnior, Ivando Amancio da; Braga, Violante Augusta Batista; Galvão, Marli Teresinha Gimeniz (Rev Rene, 2012)
Mental health promotion is an issue that deserves discussion, due to the impact of mental disorders in society. The aim was to identify the conceptions of mental health professionals on health promotion and the practice directed at users of a Psychosocial Care Center (CAPS). A qualitative approach research carried out with six top-level professionals of CAPS in Fortaleza-Ceará, Brazil. Data were collected in May 2011 through semi-structured interviews, organized and analyzed based on the Collective Subject Discourse. We extracted the main ideas, two themes emerged: health promotion and professionals practice. The subjects highlighted the expanded concept of health, principles of interdisciplinarity and intersectoriality, as well as activities to promote health of person in psychic suffering, focusing on the therapeutic relationship. The proposal contributes to the production of knowledge, building knowledge and thinking strategies to better promote health in the substitute services.